Effects of aerobic exercise combined with blood flow restriction on physical fitness and mental health of high school students - Jiang, Xianglong; Che, Tongtong (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the combined effects of aerobic exercise and Blood Flow Restriction (BFR) on physical fitness and mental health among high school students, providing empirical evidence for the reform and optimization of school physical education programs.MethodsA pre-post comparative design was adopted involving 58 high school students aged between 16 and 18 years, randomly assigned to the Teaching Intervention Group (aerobic exercise combined with BFR n = 19), Comparison Group (aerobic exercise only, n = 19), and Control Group (no additional intervention, n = 20). The intervention lasted 12 weeks, with two 45-min training sessions per week. Physical fitness indicators, including vital capacity, endurance run, 50-meter sprint, standing long jump, and sit-and-reach test, were evaluated according to the National Student Physical Fitness Standards. Mental health was assessed using the Chinese Middle School Students’ Mental Health Inventory (MMHI-60).ResultsBoth the Teaching Intervention Group and Comparison Group demonstrated significant improvements in all physical fitness indicators (ps < 0.001). However, compared to the Control Group, the Teaching Intervention Group showed significantly greater improvements in endurance run (p < 0.05, d = 0.71), 50-meter sprint (p < 0.05, d = 0.86), and standing long jump (p < 0.001, d = 0.96), along with higher improvements in sit-and-reach test (d = 2.87). Regarding mental health, the Teaching Intervention Group exhibited significantly superior effects in core indicators such as anxiety (d = 1.51), depression (d = 1.72), and academic stress (d = 1.43) compared to the Comparison Group, with a significant difference observed specifically in anxiety (p < 0.05). Correlation analysis indicated ten significant associations between physical fitness and mental health indicators in the Teaching Intervention Group, whereas only two significant correlations were identified in the Comparison Group.ConclusionAerobic exercise combined with Blood Flow Restriction effectively improves physical fitness and mental health in high school students, demonstrating greater efficacy compared to aerobic exercise alone. This combined approach also reveals a stronger synergistic promotion of physical and mental health. These findings provide new intervention perspectives for secondary school physical education, supporting BFRT as an effective instructional method in school physical education curricula.